Implementasi Strategi Pengembangan Industri Sawit dalam Menghadapi Revolusi 4.0 - Padilla Hawanda; Sri Sudiarti (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Industrial Revolution 4.0 as a new dimension of the industrial world will force companies to change in order to maintain competitiveness with other companies. The success of a country's industry in achieving these changes will determine its economy. Indonesia as a developing country is also facing the challenges of the industrial revolution 4.0 in various fields, including the palm oil industry which is Indonesia's mainstay. Research activities are carried out at the Palm Oil Research Center located in Marihat Pematang Siantar, North Sumatra. For one month, from January 16 to February 16 2023. Data and information collection was carried out using direct and indirect methods. Primary data was collected through field observations and interviews. The palm oil industry is referred to as Indonesia's super palm oil industry. The palm oil industry is one of the main sectors of the palm oil industry and has a strategic role in the Indonesian economy, facing challenges that continue to change along with the industrial revolution 4.0. The process of change and adaptation of the palm oil industry towards the Industrial Revolution 4.0 will determine Indonesia's position in the global vegetable oil competition map. The strategy for developing the palm oil industry in facing 4.0 is that in facing the Industrial 4.0 era, the palm oil industry can utilize digital technology and innovation to increase efficiency and sustainability. The palm oil industry is referred to as Indonesia's super palm oil industry. The palm oil industry is one of the main sectors of the palm oil industry and has a strategic role in the Indonesian economy, facing challenges that continue to change along with the industrial revolution 4.0. The process of change and adaptation of the palm oil industry towards the Industrial Revolution 4.0 will determine Indonesia's position in the global vegetable oil competition map. The strategy for developing the palm oil industry in facing 4.0 is that in facing the Industrial 4.0 era, the palm oil industry can utilize digital technology and innovation to increase efficiency and sustainability.